2019
DOI: 10.1177/1179573519897083
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Assessment in Acute Stroke: A Systematic Review and Meta-Analysis of Incidence, Assessment Tools, and Assessment Frequencies

Abstract: Purpose: The purpose of this systematic literature review was to examine whether different assessment methods contribute to the variance in delirium incidence detected in populations of patients with acute stroke. Specifically, the aim was to address the influence of (1) choice of assessment tool, (2) frequency of assessment, and (3) type of health professional doing the assessment. Methods: We searched MEDLINE, EMBASE, and PsycINFO and included pro- and retrospective cohort studies assessing delirium during h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…Also the severity of stroke, expressed as NIHSS score, and prestroke mRS score were associated with delirium, which is in line with previous studies [10]. In our cohort, comorbidities that were predictors of delirium were: atrial fibrillation, [32] cognitive impairment, [31] use of drugs acting on the CNS prior to hospital admission, [33,34] and leukoencephalopathy [35]. Interestingly, age was not associated with delirium, apparently in contrast with literature data.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also the severity of stroke, expressed as NIHSS score, and prestroke mRS score were associated with delirium, which is in line with previous studies [10]. In our cohort, comorbidities that were predictors of delirium were: atrial fibrillation, [32] cognitive impairment, [31] use of drugs acting on the CNS prior to hospital admission, [33,34] and leukoencephalopathy [35]. Interestingly, age was not associated with delirium, apparently in contrast with literature data.…”
Section: Discussionsupporting
confidence: 89%
“…Unexpectedly, our study showed that stroke patients affected by COPD were more prone to developing delirium. COPD is not cited among the risk factors for delirium in most of the studies analyzed in systematic reviews and meta‐analysis [13,33‐35]. Also, a recent study in a large population of stroke patients did not report COPD as a risk factor for delirium [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be appreciated that the delirium incidence of 12.5% in our study is relatively low compared to delirium incidences found in stroke populations in three systematic reviews [17,39,40]. The patients in our study had relatively minor strokes based on their NIHSS scores which may in part explain why the delirium incidence was relatively low.…”
Section: Limitationscontrasting
confidence: 49%
“…Acute stroke is often complicated by delirium [17] which pathophysiologically may be associated with changes in the sympathetic part of the autonomic nervous system [18][19][20][21][22]. We therefore hypothesized that changes in skin temperature may be linked to development of delirium in patients with acute stroke.…”
Section: Introductionmentioning
confidence: 99%